2017
DOI: 10.4314/bajopas.v9i2.39
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antibiogram of <i>Staphylococcus aureus</i> in dairy products consumed in parts of Kaduna State, Nigeria

Abstract: A total of 160 dairy products comprising of 80 each of fresh milk and 'Nono' (Fermented and defatted) were collected. The samples were cultured and identified by routine bacteriological methods. Prevalence of S.aureus (8.75%) in the products was; for fresh milk 3.75% and 'Nono' 5%. The susceptibility profile of the isolates to nine antimicrobial agents revealed a high susceptibility to Gentamicin (100%), Ciprofloxaxin (92.86%) and Chloramphenicol (92.86%). The isolates had high resistance to Tetracycline (85.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
5
8
3
Order By: Relevance
“…The resistance observed could be attributed to antibiotic abuse inform of over use and misuse of antibiotic. The antibiotic susceptibility patterns observed in this study is similar to the observations reported by Okpo et al (2016). MAR index observed in this study ranged between 0.3-0.4.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The resistance observed could be attributed to antibiotic abuse inform of over use and misuse of antibiotic. The antibiotic susceptibility patterns observed in this study is similar to the observations reported by Okpo et al (2016). MAR index observed in this study ranged between 0.3-0.4.…”
Section: Discussionsupporting
confidence: 90%
“…Isolates were grown on nutrient agar for 24 hours and colonies suspended in 2 mL sterile normal saline until a turbidity equivalent to 0.5 MacFarland standards was obtained. A 0.1 mL aliquot of each bacterial suspension was separately inoculated on freshly prepared Mueller-Hinton agar with the aid of sterile swabs to form a bacterial lawn (Okpo et al, 2016). Standard antibiotic discs were then placed on the inoculated plates equidistant from each other and pressed gently using sterile forceps to ensure contact with the agar surface.…”
Section: Antibiotic Susceptibility Testmentioning
confidence: 99%
“…The high susceptibility of these isolates to ciprofloxacin, gentamicin, and chloramphenicol was in consonance with other findings (Okpo et al , Rodrigues et al, 2017), who recorded high susceptibility Of MRSA isolated from dairy products to these three antibiotics in areas in Kaduna State, north-western Nigeria and in Brazil respectively. The ihigh iperformance iof theseiantibiotics icould bei attributed ito itheir ismallimolecularisizes, aifactorithatienhancesitheiri solubilityiinidiluents,ithusienhancingitheiripenetrationipow erithroughitheicelliwalliintoitheicytoplasmiofitheitargetiorg anismiwhereitheyiexertitheireffects (Okpo et al, 2016). This also agrees with the assertion of Maillard (2002) who opined that the high efficacy of these antibiotics in MRSA strains may be attributed to their molecular sizes.…”
Section: Discussionsupporting
confidence: 77%
“…However, higher MRSA occurrence of 12.14 and 12.60% from fresh milk and milk products in Kaduna and Zaria (which are major cities in northwestern Nigeria) were previously reported (Umaru et al, 2013;Usman and Mustapha, 2016) respectively. Similarly, our result was also lower than the 8.70% prevalence of MRSA recorded from fresh and fermented milk in parts of Kaduna State, Nigeria (Okpo et al, 2016). Furthermore, previous findings from other countries showed higher MRSA occurrence of 56, 55.26, 32 and 25.53% from dairy products in Turkey, Kenya, Algeria, and Bangladesh respectively (Patrickietial., i2013;I GundoganiandiAvci,i2014;iJahanietial., 2015; Chaalali eti al., i2016).iThe paucity of iinformation ioni MRSAi in milkiandimilkiproductsiinitheistudyiareaimadeiitidifficultitoi makeianyicomparisonianditoiassessitheileveliofiS.iaureus iinidairyiproductsiinitheiareasistudied.…”
Section: Discussioncontrasting
confidence: 46%
“…In another study by [47], some street vended foods in Ogun State Nigeria also showed the highest susceptibility of S. aureus to gentamycin. Results from [48] was also similar showing 100% susceptibility of S. aureus from dairy milk to gentamycin, and 64.29% to Trimethoprim/ Sulfamethoxazole. Previous works on S. aureus isolates from stool samples of 120 subjects from Niger Delta University, Wilberforce Island, Amassoma, Bayelsa State showed a high susceptibility of S. aureus to gentamycin which is similar to findings of this study [49].…”
Section: Multidrug-resistant Isolates Among Methicillin-resistant S mentioning
confidence: 63%